Relasi Gender, Ketahanan Keluarga dan Kualitas Pernikahan pada Keluarga Nelayan dan Buruh Tani “Brondol” Bawang Merah - Puspitawati, Herien; Azizah, Yasmin; Mulyana, Aditya; Rahmah, Azmi Faatihatur (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2019)
Previous research show that the quality of marriage is determined by harmonious gender relations and high family resilience. This study aims to analyze the influence of gender relations and family resilience on the quality of marriage in the families of farmers and fishermen. This study used a cross-sectional study design and was conducted in Pantai Sederhana Village, Bekasi Regency for participants of fishermen and Losari Lor Village, Brebes Regency for participants of peasant farmers of ‘brondol’ onions. The research participants was chosen by purposive sampling with a total sample of 130 families. The results of the independent t-test showed that fishermen's families had better gender relations compared to the families of peasant farmers. Overall, family resilience of fishermen and peasant farmers had a very significant difference. The average index of family resilience of peasant farmer families (88,9) was higher than fishermen families (83,7). The average quality of marriages of fisherman families (84,7) was better than peasant farmers families (58,6). Regression results indicate that the factors that influence the quality of marriage are gender relations, per capita income, and family resilience. Hence, the fishermen families and peasant families of red onion are expected to be able to improve gender relations whether in public, domestic and social activities as well as improve family resilience so the quality of the marriage will increase.